Constitutive Active CPK30 Interferes With Root Growth and Endomembrane Trafficking in Arabidopsis thaliana - Wang, Ren; Himschoot, Ellie; Chen, Jian; Boudsocq, Marie; Geelen, Danny; Friml, Jiří; Beeckman, Tom; Vanneste, Steffen (Frontiers in Plant Science, 2022)
Calcium-dependent protein kinases (CPK) are key components of a wide array of signaling pathways, translating stress and nutrient signaling into the modulation of cellular processes such as ion transport and transcription. However, not much is known about CPKs in endomembrane trafficking. Here, we screened for CPKs that impact on root growth and gravitropism, by overexpressing constitutively active forms of CPKs under the control of an inducible promoter in Arabidopsis. We found that inducible overexpression of an constitutive active CPK30 (CA-CPK30) resulted in a loss of root gravitropism and ectopic auxin accumulation in the root tip. Immunolocalization revealed that CA-CPK30 roots have reduced PIN protein levels, PIN1 polarity and Brefeldin A (BFA)-sensitive trafficking. Moreover, FM4-64 uptake was reduced, indicative of a defect in endocytosis. The effects on BFA-sensitive trafficking were not specific to PINs, as BFA could not induce aggregation of ARF1 and CHC-labelled endosomes in CA-CPK30. Interestingly, the interference with BFA-body formation, could be reverted by increasing the extracellular pH, indicating a pH-dependence of this CA-CPK30 effect. Altogether, our data reveal an important role for CPK30 in root growth regulation and endomembrane trafficking in Arabidopsis.